Merdeka Curriculum Formative Assessment: Analysis of Teaching Modules - Azis, Adek Cerah Kurnia; Ayudia, Alda Marsya (Jurnal Pendidikan Bahasa dan Sastra, 2024)
This research attempts to describe how accurate the implementation of formative assessments designed by teachers is through reviewing the learning plans or 'teaching modules' of the Merdeka curriculum.Methodologically, this research uses a descriptive qualitative approach to explain the position and function of formative assessment in a sample of teaching modules as well as reviewing the management and interpretation of formative assessment results. The data in this research is in the form of learning flows in teaching modules as formative assessment content of the learning process. As a research sample, the data source for this research took teaching modules from SMA Negeri 1 Tanjungbalai, SMA Negeri 1 Rowosari, and SMA Negeri 7 Medan. The data was analyzed using an application balance review process using the Merdeka curriculum assessment guidelines. The data is reconstructed if there is a discrepancy between the formative assessment applied by the teacher in the teaching module and the theory and principles of formative assessment. Then, the results of the review and reconstruction of the comparison results in the preparation of formative assessments produce conclusions in the form of a series of learning process flows which are the core of formative assessment in the teaching module.The results showed that the position of formative assessment in the three learning modules had different proportions. The proportion of formative assessment in the first module looks very small, so the reconstruction of the flow of formative assessment is carried out for five learning activities. In the second and third modules, the proportion of formative assessment is already large, so the second module only reconstructs the flow of formative assessment in one learning activity. While in the third module, the formative assessment flow was reconstructed for two learning activities.